Predictive Value of Natriuretic Peptide Tests and Ischemia Modified Albumin Levels in the Diagnosis of Obstructive Sleep Apnoea Syndrome - Hamza Ogun; Eray Metin Güler; Beyza Nur Özkan; Muhammed Yunus Bektay; Abdullah Kansu; Ömer Faruk Çalım (The Turkish Journal of Ear Nose and Throat)
Objective:To investigate the relationship between obstructive sleep apnoea (OSA) severity and oxygen desaturation with biomarkers including ischaemia-modified albumin (IMA), interleukin-1β (IL-1β), thiol/ disulphide homeostasis parameters, and cardiac biomarkers (BNP, NT-proBNP). Material and Methods:This cross-sectional study included 88 patients who underwent polysomnography at the Bezmialem Vakif University Sleep Laboratory. Participants were categorised into normal/mild OSA (n=36) and moderate/severe OSA (n=52) groups based on the apnoea-hypopnoea index (AHI). Blood samples were analysed for BNP, NT-proBNP, IMA, IL-1β, and thiol/disulphide homeostasis parameters. Results:The moderate/severe OSA group showed significantly higher levels of IMA (0.94±0.04 vs 0.88±0.04, p<0.001), IL-1β (359.82±121.14 vs 231.45±83.76 pg/mL, p<0.001), and lower levels of native thiol (345.23±69.85 vs 395.62±58.71 µmol/L, p<0.001) compared to the normal/mild group. BNP and NT-proBNP levels were moderately elevated in the moderate/severe OSA group (p=0.012 and p=0.003, respectively). Conclusion: IMA, IL-1β, and native thiol demonstrate promise as potential biomarkers for OSA severity. These findings confirm that oxidative stress and inflammation play significant roles in the pathophysi ology of OSA and offer new opportunities for diagnosis and monitoring.